RTB magnet and its manufacturing method

The R-T-B magnet with optimized elemental ratios and manufacturing process addresses the challenge of maintaining coercive force and flux stability, achieving enhanced magnetic performance and efficiency.

JP2025501463APending Publication Date: 2025-01-22BEIJING ZHONG KE SAN HUAN HI TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024534123
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-18
Filing Date
2023-03-17
Publication Date
2025-01-22

AI Technical Summary

Technical Problem

NdFeB magnets face challenges in maintaining high coercive force at elevated temperatures due to the scarcity and high cost of Dy and Tb, and existing compositions suffer from fluctuations in coercive force and residual magnetic flux.

Method used

An R-T-B magnet composition with specific elemental ratios, including Ti, B, and Ga, is developed, along with a manufacturing process involving melting, casting, hydrogen pulverization, and sintering, to create a delta phase in the grain boundary phase, enhancing coercive force and residual magnetic flux.

Benefits of technology

The magnet exhibits high residual magnetic flux and coercive force with reduced fluctuations, improved cutting efficiency, and superior magnetic properties, outperforming conventional magnets.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025501463000001_ABST
    Figure 2025501463000001_ABST
Patent Text Reader

Abstract

The present disclosure relates to an RTB magnet and a method for manufacturing the same, the elemental composition of the RTB magnet being R1 x R2 y T 100-x-y-z-u-a-b-c B z Ti u Cu a Ga b A c where R1 is a light rare earth element, the light rare earth element includes at least one of Pr and Nd, R2 is a heavy rare earth element, the heavy rare earth element includes at least one of Dy and Tb, T includes Fe and Co, A includes at least one of Al, Nb, Zr, Sn, and Mn, and x, y, z, u, a, b, and c are mass percentages and satisfy 28%≦x+y≦30.5%, 0.88%≦z≦0.92%, 0.12%≦u≦0.15%, 0≦a≦0.15%, 0.15%≦b≦0.25%, and 0≦c≦2%. The present disclosure relates to a method for synergistically adding elements such as Ti, B, and Ga to achieve R2T 17 The problem of a high proportion of phases has been solved, and the magnet now has high residual magnetic flux and high coercive force.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of rare earth permanent magnet materials, and in particular to RTB magnets and methods for their manufacture. [Background technology]

[0002] Currently, NdFeB magnets are attracting attention as functional materials necessary for energy conservation and performance improvement, and their range of applications and production volume are expanding year by year. Since they are often used at high temperatures, the requirements for magnets are becoming increasingly strict, and not only high residual magnetic flux but also high coercivity are required. On the other hand, the coercivity of NdFeB magnets decreases significantly with increasing temperature, so in order to maintain the coercivity at the operating temperature, it is necessary to improve the coercivity at room temperature.

[0003] As a method for improving the coercive force of NdFeB magnets, 14 A part of Nd in B compounds can be replaced with Dy or Tb. However, Dy and Tb have small resource reserves, and their prices are high and unstable, with a large risk of fluctuation. Therefore, there is a demand to develop a new process and a new composition for R-Fe-B magnets that have high coercivity and high residual magnetic flux while reducing the Dy and Tb content as much as possible.

[0004] Chinese Patent Specification No. 106024235 (CN106024235B) discloses an RTB sintered magnet having a composition with a Ga content of 0.3-0.8 mass%, a B content of 0.8-0.92 mass%, an Al content of 0.05-0.5 mass%, a Ti content of 0.15-0.29 mass%, and a C content of 0.10-0.30 mass%. This composition has a lower B content than conventional RTB sintered magnets, and Ga and the like are added to the magnet to obtain an R2T magnet. 17 By suppressing the formation of the RT-Ga phase, the high H cJHowever, the literature also reports that when the Ti content is less than 0.15 mass%, the variation in HcJ due to the change in the B content cannot be suppressed, and when the Ga content is less than 0.3 mass%, the amount of RT-Ga phase generated is too small, resulting in a sintered magnet having the R2T 17 Phase does not disappear and high H cJ The problem of not being able to obtain Summary of the Invention

[0005] The present invention has been made to solve the above problems, and has an object to provide a magnet that has high residual magnetic flux and high coercivity while suppressing fluctuations in magnetic coercivity.

[0006] In order to achieve the above object, the first aspect of the present disclosure provides a compound having an elemental composition of R1 x R2 y T 100-x-y-z-u-a-b-c B z Ti u Cu a Ga b A c wherein R1 is a light rare earth element including at least one of Pr and Nd, R2 is a heavy rare earth element including at least one of Dy and Tb, T includes Fe and Co, A includes at least one of Al, Nb, Zr, Sn, and Mn, and x, y, z, u, a, b, and c are mass percentages, and satisfy 28%≦x+y≦30.5%, 0.88%≦z≦0.92%, 0.12%≦u≦0.15%, 0≦a≦0.15%, 0.15%≦b≦0.25%, and 0≦c≦2%.

[0007] In the above RTB magnet of embodiment 1, it is preferable that the mass percentage of Cu element is 0.12 to 0.15%, the mass percentage of Co element is 0.5 to 2.5%, and the mass percentage of heavy metal element R2 is less than 2%.

[0008] In embodiment 1, the RTB magnet can include a main phase and a grain boundary phase, wherein the grain boundary phase includes an RTM-Ti phase having a delta phase, the RTM-Ti phase is 20-30% of the grain boundary phase, and the delta phase with R / T=0.2-0.46 is 40-50% of the RTM-Ti phase.

[0009] In aspect 1, the elemental composition of the RTM-Ti phase is R3 m R4 n T 100-m-n-v-e M v Tie, R3 is selected from Pr and / or Nd, R4 is selected from Dy and / or Tb, M includes Ga and / or other metal elements, the other metal elements being Cu and / or A, A includes at least one of Al, Nb, Zr, Sn, and Mn, T includes at least one of Fe and Co, and m, n, v, and e are atomic percentages, and satisfy 14%≦m+n≦60%, 0.1%≦v≦11%, and 0.01%≦e≦9%.

[0010] In the embodiment 1, the delta phase may have an R3+R4 content of 18 to 29 at%, a T content of 59 to 74 at%, an M content of 0.01 to 5 at%, and a Ti content of more than 1 at%.

[0011] In the embodiment 1, in the RTM-Ti phase, the grain boundary phase having a Ga / M ratio of more than 70% may account for 60 to 65% of the RTM-Ti phase.

[0012] Aspect 2 of the present invention is Step S1 of melting and casting an alloy raw material having the above elemental composition in a vacuum induction furnace to obtain an alloy sheet; Step S2 of subjecting the alloy sheet to hydrogen absorption and crushing treatment and then to fine pulverization treatment to obtain alloy fine powder; The method for producing an RTB magnet includes step S3 of placing the alloy fine powder in a magnetic field to perform orientation molding, and then performing sintering and aging treatments in a vacuum environment.

[0013] In the second embodiment, the particle size of the fine alloy powder is 3.2 to 4.2 μm.

[0014] In the second aspect, in step S1, the degree of vacuum in the vacuum induction furnace is 10 -2 ~10 -1 In step S2, the conditions for the hydrogen absorption and crushing treatment are a hydrogen absorption pressure of 0.3 to 0.4 MPa and a dehydrogenation temperature of 560 to 600°C. In the fine pulverization treatment, the pressure in the jet mill pulverization chamber is 0.5 to 0.7 MPa. In step S3, the conditions for the sintering treatment are a sintering temperature of 1000 to 1100°C and a sintering time of 5 to 8.5 h. In the aging treatment, the conditions for the aging temperature of 400 to 500°C and an aging time of 7.5 to 8.5 h.

[0015] A third aspect of the present disclosure provides an RTB magnet produced by the above method, wherein the C content in the RTB magnet is 600 to 800 ppm.

[0016] In a third embodiment, the RTB magnet has an O content of 600 to 1200 ppm and an N content of 100 to 300 ppm.

[0017] According to the above-mentioned embodiment, in the present disclosure, elements such as Ti, B, and Ga are added synergistically to generate a delta phase in the grain boundary phase, thereby improving the R2T 17 The problem of a high proportion of phases has been solved, resulting in magnets with high residual magnetic flux and high coercive force.

[0018] Other features and advantages of the present disclosure will be described in detail in the following specific embodiments. [Brief description of the drawings]

[0019] The drawings are used to provide a further understanding of the present disclosure, constitute a part of the specification, and are used to explain the present disclosure together with the following specific embodiments, but are not intended to limit the present disclosure. [Figure 1] 1 is a SEM image (points 1 to 4) of a magnet in Example 1. [Diagram 2] 1 is a SEM image (points 5 to 8) of the magnet of Example 1. [Diagram 3] 1 is a SEM image (points 9-10) of the magnet of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described in this specification are used to interpret and explain the present disclosure, and are not intended to limit the present disclosure. Note that, in this disclosure, at% is an abbreviation of atom%, that is, a percentage calculated by atomic content.

[0021] In the first embodiment of the present disclosure, the element composition is R1 x R2 y T 100-x-y-z-u-a-b B z Ti u Cu a Ga b A c wherein R1 is a light rare earth element including at least one of Pr and Nd, R2 is a heavy rare earth element including at least one of Dy and Tb, T includes Fe and Co, A includes at least one of Al, Nb, Zr, Sn, and Mn, and x, y, z, u, a, b, and c are mass percentages, and satisfy 28%≦x+y≦30.5%, 0.88%≦z≦0.92%, 0.12%≦u≦0.15%, 0≦a≦0.15%, 0.15%≦b≦0.25%, and 0≦c≦2%.

[0022] As a result of many experiments, the inventors of the present disclosure discovered that in the prior art, the Ti content is high, so Ti and B are combined to form a large number of high-strength, high-hardness TiB2 or TiB compounds at the grain boundaries, and the high hardness of TiB2 or TiB reduces the cutting efficiency during cutting. Therefore, in order to improve the cutting efficiency during batch processing, it is necessary to reduce the TiB2 or TiB content in the magnet. The H caused by a slight variation in the B content cJ The problem of large variation in RTB magnets is due to the change in the ratio of RT-Ga phase formed in the magnets at the grain boundary phase. The formation of the RT-Ga phase is sensitive to the heat treatment temperature, and non-uniform heat treatment temperature affects the formation ratio of the RT-Ga phase. This disclosure aims to adjust the elemental composition of RTB magnets by synergistically adding elements such as Ti, B, and Ga, thereby improving the RTB magnets' ... 17 The problem of a high proportion of phases has been solved, resulting in magnets with high residual magnetic flux and high coercive force.

[0023] In a preferred embodiment of the present disclosure, the mass percentage of Cu element in the RTB magnet is 0.12-0.15%, and the mass percentage of Co element is 0.5-2.5%. Furthermore, it is preferable that the content of Dy and / or Tb is less than 2%, in which case a magnet with excellent overall performance of Br>13.8kGs, HcJ>19.5kOe can be produced.

[0024] As a preferred embodiment of the present disclosure, the RTB magnet includes a main phase and a grain boundary phase, wherein the grain boundary phase includes an RTM-Ti phase having a delta phase, the RTM-Ti phase accounts for 20-30% of the grain boundary phase, and the delta phase with R / T=0.2-0.46 accounts for 40-50% of the RTM-Ti phase.

[0025] The inventors of the present disclosure further found that reducing the Ti and C content can improve the cutting efficiency of the magnet to some extent. Also, Ti can substitute for Fe atoms in the main phase. When the Ti content is high, the resulting R2T 17 The H phase of the magnet increases. cJ Therefore, reducing the Ti content may reduce R2T17 This reduces the precipitation of H cJ increases, and H cJ The variation of H cJ The reason is that although the amount of RT-Ga phase produced is reduced, the RTM-Ti phase, which has a composition similar to that of RT-Ga, is formed in the grain boundary phase of the magnet. The RTM-Ti phase, which has a Ti content of more than 1 at%, has a lower R content than the RT-Ga phase, and the RTM-Ti phase also contains a delta phase. cj The reason for the improvement is that Ti replaces part of R, resulting in the formation of a thin R-rich phase layer at the grain boundaries, which increases the spacing between grains and improves H cJ Therefore, the present disclosure proposes that the R2T is improved by synergistically adding elements such as Ti, B, and Ga to generate RTM-Ti phase and delta phase in the grain boundary phase in a specific ratio. 17 The problem of a high phase ratio has been solved, resulting in magnets with high residual magnetic flux and high coercive force.

[0026] In one specific embodiment of the present disclosure, the elemental composition of the RTM-Ti phase is R3 m R4 n T 100-m-n-v-e M v Tie, R3 is selected from Pr and / or Nd, R4 is selected from Dy and / or Tb, M includes Ga and / or other metal elements, the other metal elements being Cu and / or A, A includes at least one of Al, Nb, Zr, Sn, and Mn, and T includes Fe and Co, where m, n, v, and e are atomic percentages and satisfy 14%≦m+n≦60%, 0.1%≦v≦11%, and 0.01%≦e≦9%.

[0027] In a preferred embodiment of the present disclosure, the R3+R4 content in the delta phase of the present disclosure is in the range of 18 to 29 at%, the T content is in the range of 59 to 74 at%, the M content is in the range of 0.01 to 5 at%, and the Ti content is greater than 1 at%.

[0028] In a preferred embodiment of the present disclosure, in the RTM-Ti phase, the grain boundary phase in which Ga / M exceeds 70% accounts for 60 to 65% of the RTM-Ti phase.

[0029] A second embodiment of the present disclosure provides a method of manufacturing an RTB magnet, the method comprising: Step S1 of melting and casting an alloy raw material having the above elemental composition in a vacuum induction furnace to obtain an alloy sheet; Step S2 of subjecting the alloy sheet to hydrogen absorption and crushing treatment and then to fine pulverization treatment to obtain alloy fine powder; The method includes step S3 of placing the alloy fine powder in a magnetic field to perform orientation molding, and then performing sintering and aging treatment in a vacuum environment.

[0030] According to the present disclosure, the particle size of the alloy fine powder may be 3.2 to 4.2 μm.

[0031] According to the present disclosure, in step S1, the vacuum degree of the vacuum induction furnace is 10 -2 ~10 -1 The pressure may be 0.3-0.4 MPa, the melting temperature may be 1300-1500°C, the melting time may be 30-60 min, the casting temperature may be 1400-1500°C, and the casting time may be 10-15 min. In step S2, the conditions of the hydrogen absorption crushing process may be a hydrogen absorption pressure of 0.3-0.4 MPa, a dehydrogenation temperature of 560-600°C, and the pressure of the jet mill crushing chamber in the fine crushing process may be 0.5-0.7 MPa. In step S3, the conditions of the sintering process may be a sintering temperature of 1000-1100°C, and a sintering time of 5 h-8.5 h. The conditions of the aging process may be an aging temperature of 400-500°C, and an aging time of 7.5 h-8.5 h.

[0032] A third embodiment of the present disclosure provides an RTB magnet produced by the above method. The C content in the RTB magnet is typically 600 to 800 ppm.

[0033] The O content in the above RTB magnet may typically be 600 to 1200 ppm, and the N content may typically be 100 to 300 ppm.

[0034] The present disclosure will be described in more detail with reference to examples, but the present disclosure is not limited thereto. The raw materials used in the examples are commercially available.

[0035] Example 1 The RTB magnet of this embodiment was obtained by sequentially melting, continuous casting, hydrogen pulverization, pulverization, molding, and sintering and aging the raw materials for the RTB magnet. The specific ratios of the raw materials are shown in Table 1.

[0036] The specific manufacturing process of this embodiment is as follows. (1) Melting: Vacuum degree 7×10 -2 The melting temperature was 1400℃. (2) Continuous casting: The alloy sheet with a thickness of 0.28 mm was obtained by using the rapid solidification process. The casting temperature was 1450℃. (3) Hydrogen crushing: Hydrogen absorption was performed at a hydrogen pressure of 0.3 MPa, followed by dehydrogenation and cooling. Dehydrogenation was performed under vacuum conditions while gradually increasing the temperature, and the dehydrogenation temperature was 500°C. (4) Fine pulverization: Fine pulverization was performed in a vacuum atmosphere using a jet mill to obtain a fine powder with a particle size of 3.5 μm. The pressure in the jet mill pulverization chamber was 0.68 MPa, and after pulverization, zinc stearate, a lubricant, was added at a ratio of 0.12% of the powder weight. (5) Molding: Molding was carried out under a constant magnetic field strength and nitrogen atmosphere to obtain a green body. (6) Sintering: The compact was sintered at 1,050°C for 8 hours under vacuum conditions and then slowly air-cooled. (7) Aging: The compact was subjected to aging treatment at 500°C for 8.5 hours under vacuum conditions, and then cooled to room temperature. The magnet produced in Example 1 was subjected to a magnetic property test and a microstructure test.

[0037] Example 2 The method for producing the RTB magnet of this example was the same as that of Example 1, and the specific proportions of raw materials are shown in Table 1.

[0038] Example 3 The raw material for the RTB magnet in this example was divided into a main alloy and an auxiliary alloy, which were melted, continuously cast, hydrogen crushed, and finely crushed, respectively, and then mixed in a ratio of 4:1, and molded, sintered, and aged to obtain the RTB magnet in this example. The composition of the main alloy was R1 29 Fe 67.99 B 0.92 Ti 0.14 Cu 0.13 Ga 0.2 Co 1.62 The composition of the auxiliary alloy is R1 19 Dy 10 Fe 68.64 B 0.92 Ti 0.14 Cu 0.1 Ga 0.2 Co (R1 is Pr and Nd).

[0039] Comparative Example 1 The RTB magnet of Comparative Example 1 was produced in the same manner as in Example 1, and the specific proportions of raw materials are shown in Table 1. The Ti content was 0.16 wt%.

[0040] Comparative Example 2 The RTB magnet of Comparative Example 2 was produced in the same manner as in Example 2, and the specific proportions of raw materials are shown in Table 1. The Ga content was 0.4 wt%.

[0041] Table 1 TIFF2025501463000002.tif56170

[0042] Test Example 1 The microstructures of the RTB magnets produced in the examples and comparative examples were tested, and the specific microstructure test method involved analyzing different cross sections of the magnet with a scanning electron microscope, confirming the content of each element in the grain boundary phase of the magnet through quantitative analysis for each point (Figures 1 to 3 are SEM images of the magnet in Example 1), identifying the phases in the grain boundary triangular regions through elemental analysis, and calculating the area ratio of the phases. The content of each element at points 1 to 10 in Example 1 is shown in Table 2.

[0043] Table 2 TIFF2025501463000003.tif81170

[0044] The contents and area values ​​of each element in all grain boundary phases in the SEM images were counted, and further calculations were performed. As a result, in the grain boundary phase of the sintered magnet of Example 1, the RTM-Ti phase accounts for 22.5% of the grain boundary phase. In the grain boundary phase of the sintered magnet of Example 2, the RTM-Ti phase accounts for 26.1% of the grain boundary phase, and further, delta phase is present in the grain boundary phase. In the delta phase, the grain boundary phase with R / T=0.2 to 0.46 accounts for 47.5% of the RTM-Ti phase. In the RTM-Ti phase, the grain boundary phase with Ga / M exceeding 70% accounts for 65% of the RTM-Ti phase. In contrast, in the grain boundary phase of the sintered magnet of Comparative Example 1, the RTM-Ti phase accounts for 16.7% of the grain boundary phase, and in the delta phase, the grain boundary phase with R / T=0.2 to 0.46 accounts for only 13.2% of the RTM-Ti phase.

[0045] Test Example 2 A C content test and a magnetic property test were conducted on the RTB magnets produced in Examples 1 to 3. As a specific magnetic property test method, the test was conducted using a pulse-type BH demagnetization curve tester at room temperature of 20° C. Data on the residual magnetic flux (Br) and coercive force (HcJ) of the magnets was obtained, and the test results are shown in Table 3.

[0046] Table 3 TIFF2025501463000004.tif44170

[0047] The method for producing an RTB magnet according to the present disclosure allows the production of a magnet having a high level of residual magnetic flux and coercive force, and excellent overall performance. From the examples and comparative examples, it can be seen that the magnet produced in Example 1, in which the content of each element is within the range of the present disclosure, exhibits higher residual magnetic flux and coercive force than Comparative Example 1. Furthermore, as a result of carrying out a microstructural analysis, it is clear that an RTM-Ti phase is formed in the grain boundary phase of Example 1, and its proportion exceeds 20% of the grain boundary phase. As can be seen from the comparison between Examples 1 and 2, in the magnet of Example 2, a delta phase is formed in the grain boundary phase, and the grain boundary phase with R / T=0.2 to 0.46 forms a specific area ratio, so that a magnet having a higher total magnetic energy product and coercive force than Example 1 and having better overall performance can be obtained. Therefore, from the above examples and comparative examples, it is clear that the magnet produced according to the present disclosure has a delta phase with a specific area ratio formed in the grain boundary triangular region of the magnet. The presence of this phase is the result of the combination of the synergistic addition of Ti, B, and Ga and the corresponding manufacturing process. This phase is due to the reduction of Ti with a certain amount of B. cJ The instability problem can be suppressed, and the R2T 17 This makes it possible to suppress the formation of these phases, significantly improving the HcJ of the sintered magnet.

[0048] Furthermore, from the C content of the magnets produced in the Examples and Comparative Examples, it can be seen that the C content of the magnets produced in Examples 1 to 3 is 600 to 800 ppm, while the C content of the magnets produced in Comparative Examples 1 and 2 exceeds 900 ppm. The magnets produced in Example 1 and Comparative Example 1 were each subjected to machining. The maximum wire cutting speed of the magnet produced in Example 1 was 0.5 mm / min, while the maximum wire cutting speed of the magnet produced in Comparative Example 1 was only 0.25 mm / min, and it can be seen that the cutting efficiency of Comparative Example 1 is lower than that of Example 1. The magnet produced in Example 1 not only has excellent magnetic properties, but also has a certain degree of improvement in cutting efficiency.

[0049] Although the preferred embodiments of the present disclosure have been described in detail above, the present disclosure is not limited to the above embodiments, and various simple modifications can be made within the scope of the technical idea of ​​the present disclosure, and these also fall within the scope of protection of the present disclosure.

[0050] It should be noted that each of the specific technical features described in the above specific embodiments may be combined in any suitable manner without contradiction, and in order to avoid unnecessary repetition, the present disclosure does not separately describe the various possible combinations.

[0051] Furthermore, the different embodiments of the present disclosure may be combined in any desired manner, and unless they are contrary to the spirit of the present disclosure, they should also be considered as being included in the disclosure of the present disclosure.

Claims

1. An R-T-B magnet, The elemental composition of the R-T-B magnet is R1 x R2 y T 100-x-y-z-u-a-b-c B z Ti u Cu a G b A c wherein R1 is a light rare earth element, the light rare earth element including at least one of Pr and Nd, R2 is a heavy rare earth element, the heavy rare earth element including at least one of Dy and Tb, T includes Fe and Co, and A includes at least one of Al, Nb, Zr, Sn, and Mn, and x, y, z, u, a, b, and c are mass percentages, and satisfy the following conditions: 28%≦x+y≦30.5%, 0.88%≦z≦0.92%, 0.12%≦u≦0.15%, 0≦a≦0.15%, 0.15%≦b≦0.25%, and 0≦c≦2%.

2. The R-T-B magnet according to claim 1, characterized in that in the R-T-B magnet, the mass percentage of Cu element is 0.12-0.15%, the mass percentage of Co element is 0.5-2.5%, and preferably the mass percentage of heavy metal element R2 is less than 2%.

3. The R-T-B magnet according to claim 1, characterized in that the R-T-B magnet includes a main phase and a grain boundary phase, the grain boundary phase includes an R-T-M-Ti phase having a delta phase, the R-T-M-Ti phase accounts for 20-30% of the grain boundary phase, and the delta phase with R / T=0.2-0.46 accounts for 40-50% of the R-T-M-Ti phase.

4. The elemental composition of the R-T-M-Ti phase is R3 m R4 n T 100-m-n-v-e M v Ti e wherein R3 is selected from Pr and / or Nd, R4 is selected from Dy and / or Tb, M includes Ga and / or other metal elements, said other metal elements being Cu and / or A, A including at least one of Al, Nb, Zr, Sn, and Mn, T including Fe and Co, and m, n, v, and e are atomic percentages, and satisfy 14%≦m+n≦60%, 0.1%≦v≦11%, and 0.01%≦e≦9%.

5. The R-T-B magnet according to claim 4, characterized in that the content of R3+R4 in the delta phase is 18-29 at%, the content of T is 59-74 at%, the content of M is 0.01-5 at%, and the content of Ti is greater than 1 at%.

6. 5. The R-T-B magnet according to claim 4, wherein in the R-T-M-Ti phase, grain boundary phases in which Ga / M exceeds 70% account for 60 to 65% of the R-T-M-Ti phase.

7. Step S1 of melting and casting an alloy raw material satisfying the element composition in a vacuum induction furnace to obtain an alloy sheet; Step S2: subjecting the alloy sheet to hydrogen absorption and crushing treatment and then to fine pulverization treatment to obtain alloy fine powder; Step S3: placing the alloy fine powder in a magnetic field, shaping the powder, and then sintering and aging the powder in a vacuum environment; A method for producing an RTB magnet according to any one of claims 1 to 6, comprising:

8. In step S1, the vacuum degree of the vacuum induction furnace is 10 -2 ~10 -1 Pa, the melting temperature is 1300-1500°C, the melting time is 30-60 min, the casting temperature is 1400°C-1500°C, and the casting time is 10-15 min, In step S2, the particle size of the alloy fine powder is 3.2 to 4.2 μm, and the conditions of the hydrogen absorption and crushing treatment are a hydrogen absorption pressure of 0.3 to 0.4 MPa, a dehydrogenation temperature of 560° C. to 600° C., and a pressure in the jet mill crushing chamber in the fine crushing treatment is 0.5 to 0.7 MPa; The method according to claim 7, characterized in that in step S3, the sintering treatment conditions are a sintering temperature of 1000°C to 1100°C and a sintering time of 5h to 8.5h, and the aging treatment conditions are an aging temperature of 400°C to 500°C and an aging time of 7.5h to 8.5h.

9. 9. An RTB magnet produced by the method according to claim 7 or 8, wherein the C content in the RTB magnet is 600 to 800 ppm.

10. 10. The RTB magnet according to claim 9, wherein the O content in the RTB magnet is 600 to 1200 ppm, and the N content is 100 to 300 ppm.

Citation Information

Patent Citations

  • High-corrosion-resistance rare earth permanent magnet and preparation method thereof

    CN112562953A

  • Method for manufacturing r-t-b-based sintered magnet

    JP2015122395A

  • R-t-b based permanent magnet

    JP2018093202A

  • R-t-b based permanent magnet

    JP2019102708A